Associations between perinatal HIV-related risk factors and select serum PUFA levels among Ugandan children and adolescents - Vanessa N. Cardino; Selin Sergin; Sarah K. Zalwango; Jenifer I. Fenton; Amara E. Ezeamama (Public Health Nutrition)
Abstract